Urban fragmentation and COVID-19 in the Gauteng City Region – diverging vulnerabilities, infections and policies - Haferburg, Christoph; Ahovi, Philipp; Oßenbrügge, Jürgen (ERDKUNDE, 2022)
Urban spatial analyses of the COVID-19 pandemic try to relate the patterns of the spread of the virus to other factors, e.g. vulnerability, as supported by research on health risks of marginalized neighbourhoods. Focussing on the Gauteng City Region in South Africa, we assess whether there is a match between the effects of the pandemic, the strategies to combat the disease, and predicted vulnerabilities. While documented infection patterns are not indicating peripheral areas as most affected, disease control interventions can increase related inequalities. Reflections on South African government challenges provide the context for these concepts and strategies, suggesting that the spatial framing of health and vulnerabilities needs to be adapted.